A Spatially Selective Electroactive-Actuating Adhesive Electronics for Multi-Object Manipulation and Adaptive Haptic Interaction - Hwang, Gui Won; Jeon, Seung Hwan; Song, Jin Ho; Kim, Da Wan; Lee, Jihyun; Kim, Jae Ik; Jo, Gwanghyun; Park, Sungjun; Kim, Hye Jin; Kim, Min Seok; Yang, Tae Heon; Pang, Changhyun (Advanced Functional Materials, 2024)
Some organisms often use adhesive setae to manipulate objects or communicate critical signals for survival through subtle surface-transmitted vibrations, along with locomotion and long-term adherence. Inspired by this phenomenon, the spatially selective vibration-transmitting electronics of a multi-pixelated electroactive-actuating adhesive patch coupled with small adhesive architectures are presented. Here, diving beetle-like small dense hairs possessing concave cavities are introduced to obtain high adaptability on various non-flat surfaces in dry or wet conditions. Based on the versatile vibration-transmitting platform, the ensuing lightweight, spatially-selective, switchable-adhesive device is demonstrated to effectively manipulate multiple objects simultaneously, thus overcoming the limitations of existing monotonous transportation devices. In addition, the electronics can be applied to the stretchable skin-conforming haptic interface with high breathability and repeatable attachment capability, capable of recognizing complex outward textures of virtual objects. This skin-adaptive haptic electronics can amplify the tiny vibrotactile feedback from the diverse surface textures of virtual creatures due to its possession of bioinspired architectures at the human–machine interface. Here, the stably encapsulated device is integrated with machine learning-based comprehension for reproducible expression. Therefore, this technology offers promise in virtual reality and augmented reality applications.
Keywords: Adhesive patches; Concave cavity; Dry adhesive; Dry condition; Electro actives; Flatter surfaces; Haptic interactions; Multiobject; Non flats; Object manipulation; actuators; biomimetics; dry adhesives; flexible electronics